Uncertainty and fiscal policy in an asymmetric monetary union - Carsten Hefeker; Blandine Zimmer (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
We examine monetary and fiscal interactions in a monetary union model with uncertainty due to imperfect central bank transparency. It is first shown that monetary uncertainty discourages excessive taxation and may thus reduce average inflation and output distortions. However, as countries enter the monetary union, this tax-restraining effect of uncertainty is mitigated. The monetary union may hence lead to higher fiscal distortions in some member countries, depending on governments' spending targets and on the change in the degree of uncertainty implied by common monetary policy.
Keywords: E58; E63; F36; 330; Monetary union; fiscal policy; transparency of monetary policy; asymmetries.